Evaluation of trees in windbreaks and their effect on grazing areas at the north of Minas Gerais. Technical note - Pereira, C. M.; Zuba Junio, G. R.; Sampaio, R. A.; Alonso, Jatnel; Alvarenga, I. C.A.; Maia, C. A.; Figueredo, F. P. (Cuban Journal of Agricultural Science, 2010)
A research was conducted for two years at the Campus of the Federal University of Minas Gerais to evaluate the growth of tree species, established as windbreaks, and their effect on the protected grazing area. The windbreak was composed of two belts with two lines of trees. In the first, leucaena (Leucaena leucocephala) was sown, and, in the second, Acacia mangium. The indicators under study were: height of the plant, diameter of the stalk, diameter of the tree top, and survival. The samples were collected monthly from 100 % of the plants. Besides, the effect of the soil humidity and the speed of the wind were measured in the protected pasture area at different distances of the windbreak. The tree species evaluated were established and showed different growth habits. Leucaena only attained 2 m of height, after one year of transplantation, whereas the Acacia growth was faster, reaching height above 1.50 m at 120 d after transplantation. In all samples, the soil humidity in the protected area was always similar up to 180 m beyond the windbreak. The wind speed at 100 cm above the soil level was higher at all times and showed the same performance as at 30 cm height, indicating the start of beneficial effect of the windbreak on the wind speed. The outcomes showed that the tree species under study had different and favorable growth characteristics allowing their use in the formation of windbreaks in grazing areas as another alternative to the use of these species in silvopastoral systems. Key words: trees, windbreaks, silvopastoral systems, legumes.